2D and 3D Geovisualization: Learning user Preferences in Landslide Vulnerability - Wahyudi, Hafif Bustani; Ramdani, Fatwa; Bachtiar, Fitra Abdurrachman (Journal of Information Technology and Computer Science, 2020)
Landslides often cause impacts on the environment, infrastructure, and society. The impacts of landslides can be minimized by creating disaster awareness. Landslide vulnerability mapping can be used as a dissemination media to increase disaster awareness. The mapping methods that can be used are 2D and 3D geovisualization. There is very few research in current literature explaining the user preferences on geovisualization 2D and 3D related to landslide vulnerability.Â  In this paper, the user preferences of both 2D and 3D geovisualization will be evaluated. This study will focus to find out which geovisualization suits most users and their literacy spatial among those provided geovisualizations. From our results, 90% of users prefer 3D geovisualization over 2D. Furthermore, our analysis shows that 2D geovisualization has the advantage of being easily understood by users in all ages. Meanwhile, 3D geovisualization is better at increasing users' spatial literacy at all ages and levels of education in knowing the causes of landslide vulnerability. Appropriate geovisualization will provide information and knowledge that is useful for communities in regards of landslide vulnerability for better disaster awareness